PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Achyani, Fatchan; Lestari, Susi (Riset Akuntansi dan Keuangan Indonesia, 2019)
This study aims to examine the effect of tax planning on earnings management. In addition, several factors that are thougt to also affect earnings management are also tested, among others: deferred tax expense, deferred tax assets, managerial ownership, and free cash flow. The data used in this study is the annual report of companies listed on Indonesia Stock Exchange in the period 2015-2017. Jones modifications are used to measure earnings management. This study uses multiple regression analysis tools. The results showed that only free cash flow can affect earnings management while tax planning, deferred tax expense, deferred tax assets, and managerial ownership do not affect earnings management.